Perception of the dirun village community, Lamaknen district towards nature tourism management in the Fulan Fehan tourism area - Berek, Apriani; Elim, Ramses V.; Kristinawanti, Ika; Manek, Luisa Moi; Ora, Yudhistira A.N.R (Central Research Institute For Agriculture, 2024)
Fulan Fehan Nature Tourism Area is managed by the Technical Implementation Unit of the Forest Management Unit of Belu Regency. The management of Fulan Fehan Nature Tourism has great functions and benefits for the people of Dirun Village so that it is hoped that the community will continue to maintain and preserve the Fulan Fehan Nature Tourism location. However, the problem is that there is no information and data regarding the community's perception of the management of the nature tourism area so that community perception is important to study because in the perception process, individuals are required to provide positive, negative, and so on. This study aims to determine the characteristics of the Dirun Village community and analyze the perceptions of the Dirun Village community in the management of the Fulan Fehan Nature Tourism area. The data collection technique was carried out using a questionnaire that had been prepared according to the objectives and the analysis used was percentage analysis and a Likert scale. The results of the study showedRespondent characteristics based on gender are dominated by menwhich is 62% or 54 respondents. Respondents based on age are dominated by people aged 17-40 years (early adulthood). The last education of respondents is dominated by high school education as much as 34% or 30 respondents. Based on their occupation, respondents are dominated by farmers, namely 24% or 21 respondents. The average recapitulation of community perceptions of natural tourism management in Fulan Fehan is 2.70, meaning that the people of Dirun Village consider the existence of the area to be good and have a positive impact on the community.